The Effectiveness of Gum and Mint Candy in Quitting Smoking in Adolescents - Nanik Sayidatul Fauziyah; Mustiah Yulistiani (UM Purwokerto Press, 2022)
Background: Smoking is a bad habit that can cause various diseases for a long-term period with high frequency. Adolescents are the nation's assets and are expected to have optimal health status. Thus, it is necessary to make efforts to quit smoking, such as the use of gum and mint candy as a substitute for cigarettes to reduce the number of cigarette consumption or even stop smoking behavior in adolescents. Objective: This study aimed to determine the differences in the effectiveness of chewing gum and mint candy on quitting smoking in adolescents. Methods: This was quantitative research with a quasi-experimental design. The sample was 62 students of SMK Ma'arif 1 Kroya who were selected through a simple random sampling method. Then, survey sheets and observation books were used as the instruments. Afterward, the data were analyzed using the Wilcoxon test and Mann-Whitney test. Results: The result of the Wilcoxon test indicated that the number of cigarette consumption before and after the gum intervention was 0.001. meanwhile, the number of cigarette consumption before and after the intervention of mint candy was 0.003. It meant that both were effective in qutting smoking efforts. In addition, the result of the Mann-Whitney test was 0.070. It meant no difference in the effectiveness of gum and mint candy on qutting smoking in adolescents. Conclusion: There was no significant difference between the gum and mint candy in quitting smoking cigarettes in the adolescent.